Extracellular accumulation of a new amino acid, O-2-hydroxypropylhomoserine, from 1,2-propanediol by flavobacterium rigense. - Yamada, S (1978)
During an investigation of microorganisms utilizing petrochemicals, a strain identified as Flavobacterium rigense was found to accumulate a new amino acid in a medium containing 1,2-propanediol as the sole carbon source. Cultural conditions for the accumulation of the product were investigated, and as a result, the yield was increased to 2.8 mg/ml after a 5-day incubation in a medium containing 8% 1,2-propanediol. The pure amino acid was isolated, and its structure was investigated. Elemental analysis and infrared, nuclear magnetic resonance, and mass spectral analyses indicated that the amino acids is O-2-hydroxypropylhomoserine.